Pengaruh Variasi Pembukaan Sudu Pengarah Terhadap Efisiensi Turbin CROSS FLOW = The Effects of Opening Variation of Guide Vane on the Efficiency of Cross Flow Turbine - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2004)
This research was intended to study the effects of opening variation of guide vane on output power, efficiency, and the characteristic of a cross flow turbine. A Cross flow turbine was installed at a flow system which had a head of 5.48 m. The guide vane consisted. of 2 segments with lengths of 28 mm dan 56 mm. The opening of both seginerits can be varied in three positions, e.g :1/3, 2/3, and 3/3. At each opening position, the guide vane direction relative to the runner vane can also be varied to have an angle of 15, 30, 45, and 60°. This research was carried out for 2 different rotors with number of vanes of 23 and 33. The runner diameter and length were 110 mm and 84 zrun, respectively. The water flow rate was also varied at : 4, 5, 6, 7, and 8 litre/second. The result of the research showed that the maximum efficiency and output power with guide vane opening of 1/3 for both runner were not significant, the maximum efficiency and output power were lower than 10% and 30 watts, respectively. For 23 vanes runner the guide vane opening of 2/3 gives a maximum efficiency about 13.93% with the opening angle of 45° and 8 litre/second flow rate. While, for the 33 vanes runner with the similar guide vane position and flow rate the maximum efficiency was slightly lower. The efficiency was 11.76%. For 23 vanes runner the guide vane opening was changed to 3/3 gives a maximum efficiency of 11.12% with the opening angle 45° and 8 litre/second flow rate. While, for the 33 vane runner with the similar guide vane position and flow rate the maximum efficiency was slightly higher. The efficiency was 13.48%.